Intra-FCY1: a novel system to identify mutations that cause protein misfolding - Quan, N.; Eguchi, Y.; Geiler-Samerotte, K. (Frontiers in Genetics, 2023)
Most mutations to coding sequences increase the propensity of the encoded protein to misfold. Despite the importance of protein misfolding in human disease and protein evolution, there are fundamental questions that remain unanswered, such as, which mutations cause the most misfolding? These questions are difficult because we lack high-throughput methods to compare the destabilizing effects of different mutations. Here, we present a novel in vivo system named Intra-FCY1 that we use to identify mutations that cause misfolding of a model protein (yellow fluorescent protein (YFP)) in Saccharomyces cerevisiae. The Intra-FCY1 system utilizes two complementary fragments of the yeast cytosine deaminase Fcy1, a toxic protein, into which YFP is inserted. When YFP folds, the Fcy1 fragments associate together to reconstitute their function, conferring toxicity in media containing 5-fluorocytosine and hindering growth. But mutations that make YFP misfold abrogate Fcy1 toxicity, thus strains possessing misfolded YFP variants rise to high frequency in growth competition experiments. This makes such strains easier to study. The Intra-FCY1 system cancels localization of the protein of interest, thus can be applied to study the relative stability of mutant versions of diverse cellular proteins. Here, we confirm this method can identify novel mutations that cause misfolding, highlighting the potential for Intra-FCY1 to illuminate the relationship between protein sequence and stability.High-throughput screens have been useful in identifying and characterizing mutations that improve protein stability. Often, these screens are less sensitive when it comes to identifying destabilizing mutations. Nonetheless, destabilizing mutations are important because they are implicated in misfolded protein associated disease and because they have a huge impact on protein evolution. Here, we present a method that reverses the technique used to identify stabilizing mutations such that the mutations that cause protein misfolding can be characterized in high-throughput. Our method covalently binds a protein of interest to a toxic reporter protein.When the protein of interest misfolds, it disrupts function of the toxic reporter, thus rescuing cells from the growth defect it imposes. In this way, cells possessing misfolded variants of the protein of interest rise to higher frequency in a fitness competition.